How communication is used to perpetuate mutedness of women in the police force a case study of San Pedro Police station, Davao city - Germina, Divina Amor J.
This study describes how communication is used to perpetuate the mutedness of women in the Women and Children's Protective Desk division in San Pedro police station. The research utilizes qualitative interviews that explored the roles female officers adopt in police work, the process they create to negotiate the expectation of their roles, and their ability or inability to integrate into the police culture based on these choices. Through the antenarrative-descriptive method, this study describes realities in which women in the police force exist using Cheris Kramarae's Muted Group Theory, identifies the current communication barriers at work in the police station that result in organizational conflict, and how it affects performance of the female police officers in the Women and Children's Protective Desk. This study shows important implications for female officers, police administrators and community members as police agencies across the nation face police recruitment shortages, accompanied by the community demand for a ?new breed? of police officers that embodies communication, problem solving, and greater sensitivity.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication